Developing Wearable Technologies to Advance Understanding of Precision Environmental Health: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The rapid proliferation of wearable devices that gather data on physical activity and physiology has become commonplace across various sectors of society. Concurrently, the development of advanced wearables and sensors capable of detecting a multitude of compounds presents new opportunities for monitoring environmental exposure risks. Wearable technologies are additionally showing promise in disease prediction, detection, and management, thereby offering potential advancements in the interdisciplinary fields of both environmental health and biomedicine. To gain insight into this burgeoning field, on June 1 and 2, 2023, the National Academies of Sciences, Engineering, and Medicine organized a 2-day virtual workshop titled Developing Wearable Technologies to Advance Understanding of Precision Environmental Health. Experts from government, industry, and academia convened to discuss emerging applications and the latest advances in wearable technologies. The workshop aimed to explore the potential of wearables in capturing, monitoring, and predicting environmental exposures and risks to inform precision environmental health.
Keywords: Environment and Environmental Studies; Behavioral and Social Sciences; Health and Medicine

Children's Environmental Health: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The National Academies Board on Population Health and Public Health Practice, Board on Environmental Studies and Toxicology, and Board on Children Youth and Families convened a workshop in August 2022 to explore the impact of specific environmental exposures in utero, infancy, early childhood, and adolescence. Experts in epidemiology, toxicology, dose response methodology, and exposure science explored gaps in knowledge around vulnerabilities to environmental hazards as well as opportunities to inform public policy moving forward. This Proceedings of the workshop summarizes important discussions held during the virtual event and outlines recommendations for ways the Environmental Protection Agency can incorporate new research methods into its risk assessments.
Keywords: Health and Medicine; Environment and Environmental Studies

Integrating Public and Ecosystem Health Systems to Foster Resilience: A Workshop to Identify Research to Bridge the Knowledge-to-Action Gap: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Ecosystems form the foundation upon which society can survive and thrive, providing food, water, air, materials, and recreation. These connections between people and their environments are under stress from human-driven climate change, pollution, resource exploitation, and other actions that may have implications for public health. The integral connection between nature and human health is recognized and has been explored through different bodies of work; however, because of the breadth of this issue, many implications regarding public health are not well characterized. This has created a gap in understanding the interconnections between public health and ecosystem health systems and how ecosystem resiliency may affect public health. To inform the development of a research agenda aimed at bridging the knowledge-to-action gap related to integrating public and ecological health to foster resilience, the National Academies of Sciences, Engineering, and Medicine held a workshop across three days that brought together interdisciplinary researchers and practitioners from the public health, natural resource management, and environmental protection communities to exchange knowledge, discuss critical gaps in understanding and practice, and identify promising research that could support the development of domestic and international policy and practice. Day 1 of the workshop, held on September 19, 2022, addressed the following question: What has been learned about how to integrate public health and nature into research, policy, and practice to foster resilience? Days 2 and 3, held on September 29 and 30, 2022, explored advancement opportunities in transdisciplinary and community-engaged scholarship to improve integration of public health and nature and inform policy and practice and opportunities to bridge the knowledge-to-action gap with strategies to translate knowledge into policy and practice. This publication summarizes the presentation and discussion of the workshop.
Keywords: Environment and Environmental Studies; Health and Medicine

Communities, Climate Change, and Health Equity: Lessons Learned in Addressing Inequities in Heat-Related Climate Change Impacts: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Extreme heat is a pervasive and critical hazard of climate change. While heat poses a significant threat to large swaths of the human population, it is not affecting all people or all communities equally. To explore what it takes to prevent and mitigate inequitable health impacts from extreme heat, the National Academies Environmental Health Matters Initiative (EHMI) organized a workshop on June 20-21, 2023, titled Communities, Climate Change, and Health Equity: Lessons Learned in Addressing Inequities in Heat-Related Climate Change Impacts. The workshop was the third in a series of EHMI events exploring the state of knowledge about climate-related health disparities. This hybrid event convened people with lived experience in communities affected by extreme heat; experts in environmental health, economic, and racial justice; climate scientists; energy specialists; and people involved in sustainable planning and disaster relief. Through presentations, shared stories, and interactive discussions, participants explored real-world challenges related to extreme heat, along with actions being pursued to prevent, adapt to, or mitigate the health consequences.
Keywords: Environment and Environmental Studies; Health and Medicine

The Interplay Between Environmental Exposures and Mental Health Outcomes: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Mounting evidence shows that the environment can play an important role in mental health, yet comparatively few studies have focused on the mental or behavioral health outcomes of environmental stressors. The Interplay Between Environmental Exposures and Mental Health Outcomes, a virtual workshop held on February 2-3, 2021, provided mental health and environmental health research experts from government, academia, and the private sector with the opportunity to explore emerging research on the relationships between environmental exposures and mental health. Workshop presentations covered a broad array of the diverse makeup of environmental exposures, including those that are chemical, biological, or physical, and either natural or human-made in origin. Furthermore, while the historical definition of an environmental exposure refers to a contact that causes a negative health effect, some presenters highlighted how a person's environment can lead to positive mental health outcomes. Workshop participants also discussed approaches to better integrate mental and behavioral health into multidisciplinary considerations of environmental health; considered how mental and behavioral health impacts could become part of environmental risk assessments and public health choices; and highlighted new tools and technologies to assess ways in which the environment can affect mental health. This Proceedings of a Workshop-in Brief provides the rapporteurs' high-level summary of the topics addressed in the workshop and suggestions provided by workshop participants for ways of integrating mental and behavioral health research and environmental research.
Keywords: Environment and Environmental Studies; Health and Medicine

Environmental Neuroscience: Advancing the Understanding of How Chemical Exposures Impact Brain Health and Disease: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Humans are potentially exposed to more than 80,000 toxic chemicals in the environment, yet their impacts on brain health and disease are not well understood. The sheer number of these chemicals has overwhelmed the ability to determine their individual toxicity, much less potential interactive effects. Early life exposures to chemicals can have permanent consequences for neurodevelopment and for neurodegeneration in later life. Toxic effects resulting from chemical exposure can interact with other risk factors such as prenatal stress, and persistence of some chemicals in the brain over time may result in cumulative toxicity. Because neurodevelopmental and neurodegenerative disorders - such as attention-deficit hyperactivity disorder and Parkinson's disease - cannot be fully explained by genetic risk factors alone, understanding the role of individual environmental chemical exposures is critical. On June 25, 2020, the National Academies of Sciences, Engineering, and Medicine's Forum on Neuroscience and Nervous System Disorders hosted a workshop to lay the foundation for future advances in environmental neuroscience. The workshop was designed to explore new opportunities to bridge the gap between what is known about the genetic contribution to brain disorders and what is known, and not known, about the contribution of environmental influences, as well as to discuss what is known about how genetic and environmental factors interact. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

Toward Understanding the Interplay of Environmental Stressors, Infectious Diseases, and Human Health: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Infectious diseases are among the top five leading causes of death worldwide. Scientists have long known that the environment plays a defining role in the emergence and spread of infectious diseases. However, the relationships among human exposures to environmental pollution; rapid environmental change; and the emergence, spread, and persistence of infectious diseases are not yet well understood. Emerging findings suggest that exposure to environmental pollutants such as airborne particulate matter, industrial chemicals, and heavy metals may alter the immune system, increasing human susceptibility to infection. New research findings show that the microbiome of humans and ecosystems also play important roles in infection. Nonetheless, the fields of environmental health and infectious diseases largely operate distinctly from one another even though research on the interplay between these fields could inform new health practices, public health research, and public health policy. On January 15–16, 2019, the National Academies of Sciences, Engineering, and Medicine held a 2-day workshop to explore emerging evidence on the interactions among environmental stressors, infectious diseases, and human health. The workshop brought together a multidisciplinary group, including experts in infectious disease, global public health, toxicology, epidemiology, and science policy, to discuss the emerging science and its implications for decisions about research and public policy. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Review of the Draft NTP Monograph: Systematic Review of Fluoride Exposure and Neurodevelopmental and Cognitive Health Effects - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Toxicology Program (NTP) conducted a systematic review of the evidence of adverse neurodevelopmental and cognitive effects of fluoride exposure. NTP's conclusions are summarized in the monograph Systematic Review of Fluoride Exposure and Neurodevelopmental and Cognitive Health Effects. At the request of NTP, a committee convened by the National Academies reviewed their monograph to ensure the integrity of that report. It is important to note that the committee was tasked with reviewing the monograph and focused its efforts on evaluating whether evidence as presented in the monograph supported NTP's conclusions. Thus, it did not conduct its own independent evaluation of the evidence, and it did not conduct a data audit. However, it did review some key literature to enable its review of the monograph. Review of the Draft NTP Monograph contains findings and suggestions for improvements and some overarching findings concerning methods, assessment of animal and human evidence, and NTP's hazard conclusion.
Keywords: Environment and Environmental Studies; Health and Medicine

Review of Fate, Exposure, and Effects of Sunscreens in Aquatic Environments and Implications for Sunscreen Usage and Human Health - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Regular use of sunscreens has been shown to reduce the risk of sunburn and skin cancer, and slow photoaging of skin. Sunscreens can rinse off into water where people are swimming or wading, and can also enter bodies of water through wastewater such as from bathing or showering. As a result, the ultraviolet (UV) filters - the active ingredients in sunscreens that reduce the amount of UV radiation on skin - have been detected in the water, sediment, and animal tissues in aquatic environments. Because the impact of these filters on aquatic ecosystems is not fully understood, assessment is needed to better understand their environmental impacts. This report calls on the U.S. Environmental Protection Agency to conduct an ecological risk assessment of UV filters to characterize the possible risks to aquatic ecosystems and the species that live in them. EPA should focus on environments more likely to be exposed such as those with heavy recreational use, or where wastewater and urban runoff enter the water. The risk assessment should cover a broad range of species and biological effects and could consider potential interacting effects among UV filters and with other environmental stresses such as climate change. In addition, the report describes the role of sunscreens in preventing skin cancer and what is known about how human health could be affected by potential changes in usage. While the need for a risk assessment is urgent, research is needed to advance understanding of both risks to the environment from UV filters and impacts to human health from changing sunscreen availability and usage.
Keywords: Environment and Environmental Studies; Health and Medicine

Integrating the Science of Aging and Environmental Health Research: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Understanding and ensuring healthy aging has become increasingly important as the human life span increases with each decade. The need to better understand the role of environmental exposures in the development of aging-related diseases, such as cardiovascular disease, cancer, and dementia, is now an important driver for research at the intersection of aging and environmental health. With that in mind, on June 9-10, 2020, the Standing Committee on the Use of Emerging Science for Environmental Health Decisions of the National Academies of Sciences, Engineering, and Medicine held a 1.5-day workshop to explore how environmental exposures influence or mediate aging and how aging influences environmentally mediated health outcomes. The workshop brought together a multidisciplinary group of experts who described the current state of knowledge in the field as well as ideas for next steps including research opportunities and needs, enabling technologies and analytical tools, and mechanisms to anticipate and use new data to inform environmental health decisions. This Proceedings of a Workshop in Brief summarizes the invited speakers' presentations and the discussion periods that followed each session.
Keywords: Environment and Environmental Studies; Health and Medicine

Companion Animals as Sentinels for Predicting Environmental Exposure Effects on Aging and Cancer Susceptibility in Humans: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
To examine the potential role of companion animals as sentinels of relevant, shared environmental exposures that may affect human aging and cancer, the National Cancer Policy Forum held a workshop in collaboration with the Forum on Aging, Disability, and Independence and the Standing Committee on the Use of Emerging Science for Environmental Health Decisions to explore this promising and underutilized pathway for research. Presentations and panel discussions covered the current state of the science and pathways for accelerating research, along with opportunities and challenges for using this novel translational approach to exposure science to advance human health. This Proceedings of a Workshop outlines the presentations and discussions that occurred during the workshop.
Keywords: Health and Medicine; Environment and Environmental Studies

Guidance on PFAS Exposure, Testing, and Clinical Follow-Up - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
In thousands of communities across the United States, drinking water is contaminated with chemicals known as perfluoroalkyl and polyfluoroalkyl substances (PFAS). PFAS are used in a wide range of products, such as non-stick cookware, water and stain repellent fabrics, and fire-fighting foam, because they have properties that repel oil and water, reduce friction, and resist temperature changes. PFAS can leak into the environment where they are made, used, disposed of, or spilled. PFAS exposure has been linked to a number of adverse health effects including certain cancers, thyroid dysfunction, changes in cholesterol, and small reductions in birth weight. This report recommends that the Centers for Disease Control and Prevention (CDC) update its clinical guidance to advise clinicians to offer PFAS blood testing to patients who are likely to have a history of elevated exposure, such as those with occupational exposures or those who live in areas known to be contaminated. If testing reveals PFAS levels associated with an increased risk of adverse effects, patients should receive regular screenings and monitoring for these and other health impacts. Guidance on PFAS Exposure, Testing, and Clinical Follow-Up recommends that the CDC, Agency for Toxic Substances and Disease Registry (ATSDR), and public health departments support clinicians by creating educational materials on PFAS exposure, potential health effects, the limitations of testing, and the benefits and harms of testing.
Keywords: Environment and Environmental Studies; Health and Medicine

Review of Report and Approach to Evaluating Long-Term Health Effects in Army Test Subjects: Interim Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Between 1942 and 1975, the U.S. Army conducted tests with human subjects to study the effects of a variety of agents, including chemical warfare and biological agents. The potential long-term health effects on the test subjects from their exposures have been evaluated periodically, most recently in a report titled Assessment of Potential Long-Term Health Effects on Army Human Test Subjects of Relevant Biological and Chemical Agents, Drugs, Medications and Substances: Literature Review and Analysis (the Report), which was prepared by a contractor to assist the Army with making determinations about providing medical care to former test subjects. In response to a request by the Army, the National Academies of Sciences, Engineering, and Medicine formed a committee that was tasked with examining whether the Report appropriately identified potential long-term health effects from exposure to the test agents and whether an adequate weight-of-evidence approach was used to characterize the strength of the associations between the agents and their potential health effects. The committee was made aware at its first meeting on November 30, 2017, that the Army had already begun to receive applications for medical care and that some determinations may need to be made before the committee's evaluation of the Report was completed. Because of this urgency, the Army developed a process by which applications for medical care will be reviewed, and as a result, the committee was given the additional task of reviewing the Army's Memorandum that describes the approach that will be used by the Army to evaluate agent- and outcome-specific associations. This interim report was prepared to facilitate the Army's deliberations. A review of the Report is presented first, followed by a review of the Memorandum.
Keywords: Health and Medicine

Acute Exposure Guideline Levels for Selected Airborne Chemicals: Volume 11 - National Research Council (The National Academies Press, 2012)
At the request of the Department of Defense and the Environmental Protection Agency, the National Research Council has reviewed the relevant scientific literature compiled by an expert panel and established Acute Exposure Guideline Levels (AEGLs) for several chemicals. AEGLs represent exposure levels below which adverse health effects are not likely to occur and are useful in responding to emergencies, such as accidental or intentional chemical releases in community, workplace, transportation, and military settings, and for the remediation of contaminated sites. Three AEGLs are approved for each chemical, representing exposure levels that result in: 1) notable but reversible discomfort; 2) long-lasting health effects; and 3) life-threatening health impacts. This volume in the series includes AEGLs for bis-chloromethyl ether, chloromethyl methyl ether, chlorosilanes, nitrogen oxides, and vinyl chloride.
Keywords: Environment and Environmental Studies; Health and Medicine

Letter Report on the Development of a Model for Ranking FDA Product Categories on the Basis of Health Risks - National Research Council; Institute of Medicine (The National Academies Press, 2009)
Keywords: Health and Medicine

Space Radiation and Astronaut Health: Managing and Communicating Cancer Risks - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
Astronauts face unique health-related risks during crewed space missions, and longer-duration missions that extend to greater distances in our solar system (including to the Moon and Mars) will likely increase those risks. Cancer risks due to ionizing radiation exposure are one of these health-related risks. Assessing, managing, and communicating radiation-induced cancer risks associated with spaceflight are challenging because of incomplete knowledge of the radiation environment in space, limited data on radiation-induced cellular damage mechanisms, lack of direct observations from epidemiological studies, and the complexities of understanding radiation risk. At the request of the National Aeronautics and Space Administration (NASA), an ad hoc committee of the National Academies of Sciences, Engineering, and Medicine convened to provide advice on NASA's proposed updates to their space radiation health standard, which sets the allowable limit of space radiation exposure throughout the course of an astronaut's career. Space Radiation and Astronaut Health: Managing and Communicating Cancer Risks provides the committee's recommendations and conclusions regarding the updated space radiation health standard, NASA's radiation risk communication strategies, and a process for developing an ethics-informed waiver protocol for long-duration spaceflight missions.
Keywords: Environment and Environmental Studies; Health and Medicine

Wastewater-based Disease Surveillance for Public Health Action - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic spurred a rapid expansion of wastewater-based infectious disease surveillance systems to monitor and anticipate disease trends in communities.The Centers for Disease Control and Prevention (CDC) launched the National Wastewater Surveillance System in September 2020 to help coordinate and build upon those efforts. Produced at the request of CDC, this report reviews the usefulness of community-level wastewater surveillance during the pandemic and assesses its potential value for control and prevention of infectious diseases beyond COVID-19. Wastewater-based Disease Surveillance for Public Health Action concludes that wastewater surveillance is and will continue to be a valuable component of infectious disease management. This report presents a vision for a national wastewater surveillance system that would track multiple pathogens simultaneously and pivot quickly to detect emerging pathogens, and it offers recommendations to ensure that the system is flexible, equitable, and economically sustainable for informing public health actions. The report also recommends approaches to address ethical and privacy concerns and develop a more representative wastewater surveillance system. Predictable and sustained federal funding as well as ongoing coordination and collaboration among many partners will be critical to the effectiveness of efforts moving forward.
Keywords: Environment and Environmental Studies; Health and Medicine

Managing Health Effects of Beryllium Exposure - National Research Council (The National Academies Press, 2008)
Beryllium is a lightweight metal that is used for its exceptional strength and high heat-absorbing capability. Beryllium and its alloys can be found in many important technologies in the defense and aeronautics industries, such as nuclear devices, satellite systems, radar systems, and aircraft bushings and bearings. Pulmonary disease associated with exposure to beryllium has been recognized and studied since the early 1940s, and an occupational guideline for limiting exposure to beryllium has been in place since 1949. Over the last few decades, much has been learned about chronic beryllium disease and factors that contribute to its occurrence in exposed people. Despite reduced workplace exposure, chronic beryllium disease continues to occur. Those developments have led to debates about the adequacy of the long-standing occupational exposure limit for protecting worker health. This book, requested by the U.S. Air Force to help to determine the steps necessary to protect its workforce from the effects of beryllium used in military aerospace applications, reviews the scientific literature on beryllium and outlines an exposure and disease management program for its protecting workers.
Keywords: Health and Medicine

Contaminated Water Supplies at Camp Lejeune: Assessing Potential Health Effects - National Research Council (The National Academies Press, 2009)
In the early 1980s, two water-supply systems on the Marine Corps Base Camp Lejeune in North Carolina were found to be contaminated with the industrial solvents trichloroethylene (TCE) and perchloroethylene (PCE). The water systems were supplied by the Tarawa Terrace and Hadnot Point watertreatment plants, which served enlisted-family housing, barracks for unmarried service personnel, base administrative offices, schools, and recreational areas. The Hadnot Point water system also served the base hospital and an industrial area and supplied water to housing on the Holcomb Boulevard water system (full-time until 1972 and periodically thereafter). This book examines what is known about the contamination of the water supplies at Camp Lejeune and whether the contamination can be linked to any adverse health outcomes in former residents and workers at the base.
Keywords: Health and Medicine

Review of Studies of Possible Toxic Effects from Past Environmental Contamination at Fort Detrick: A Letter Report - National Research Council (The National Academies Press, 2012)
Keywords: Environment and Environmental Studies; Health and Medicine